The Role of Disclosure in Green Finance - Tobias Trog̈er; Sebastian Steuer (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
We study the design features of disclosure regulations that seek to trigger the green transition of the global economy and ask whether such regulatory interventions are likely to bring about sufficient market discipline to achieve socially optimal climate targets. We categorize the transparency obligations stipulated in green finance regulation as either compelling the standardized disclosure of raw data, or providing quality labels that signal desirable green characteristics of investment products based on a uniform methodology. Both categories of transparency requirements can be imposed at activity, issuer, and portfolio level. Finance theory and empirical evidence suggest that investors may prefer "green" over "dirty" assets for both financial and non-financial reasons and may thus demand higher returns from environmentally-harmful investment opportunities. However, the market discipline that this negative cost of capital effect exerts on "dirty" issuers is potentially attenuated by countervailing investor interests and does not automatically lead to socially optimal outcomes. Mandatory disclosure obligations and their (public) enforcement can play an important role in green finance strategies. They prevent an underproduction of the standardized high-quality information that investors need in order to allocate capital according to their preferences. However, the rationale behind regulatory intervention is not equally strong for all categories and all levels of "green" disclosure obligations. Corporate governance problems and other agency conflicts in intermediated investment chains do not represent a categorical impediment for green finance strategies. However, the many forces that may prevent markets from achieving socially optimal equilibria render disclosure-centered green finance legislation a second best to more direct forms of regulatory intervention like global carbon taxation and emissions trading schemes. Inherently transnational market-based green finance concepts can play a supporting role in sustainable transition, which is particularly important as long as first-best solutions remain politically unavailable.
urn:nbn:de:hebis:30:3-615542
Keywords: D4; D6; G1; G3; G4; K2; 330; green finance; sustainable finance; ESG; mandatory disclosure; taxonomies; benchmarks; labels; asset pricing; market discipline; climate change; climate risk